New modified Chua’s circuit and experiment - WANG Fa-qiang; LIU Chong-xin (Tongxin xuebao)
A new modified Chua’s circuit was presented and its chaotic properties were studied in theoretic. The condi-tion of occurring Hopf bifurcation was derived and some phase portraits were given. And then, an electronic circuit was designed to realize this modified Chua’s circuit. Some phase portraits are demonstrated not only by computer simulation but also by the circuit experiment.